Eksistensi Pesantren dalam Pembentukan Kepribadian Santri - Wiwin Fitriyah; Abd Hamid Wahid; Chusnul Muali (PALAPA, 2018)
Pesantren education essentially grows and develops based on religious motivation. The purpose is to streamline broadcasting efforts (da’wah) and practice of Islamic teaching. In its implementation, it undertook the processn of fostering knowledge, attitudes and skills thatbconcern the religious aspect. So the formation of a virtuous man (al akhlaqul karimah)is in line with a consistent religious practice or istiqomah. Therefore , pondok pesantren has to print the true human expert in the field of religion (tafaqquh fiddin, transfer knowledge to society and create good person. From there embedded the formation of good morality is the power of the soul from within that encourages people to do good and prevent bad deeds, enjoin the ma’ruf and prevent the evil. From here the behavior of good behavior (akhlaq al-karimah) which will become the character of his personality. Related to the formationof personality, there is the problem of students who become measurement of success or not about the coaching personality of santri.